2009
DOI: 10.1177/0002716209334435
|View full text |Cite
|
Sign up to set email alerts
|

Competing Scenarios for European Fathers: Applying Sen's Capabilities and Agency Framework to Work—Family Balance

Abstract: European policy and discourse create crosscurrents for fathers: the promotion of work-family balance (WFB) and more involved fathering versus work-focused competitiveness and productivity goals in globalized economies. Using Amartya Sen's capabilities and agency paradigm, the authors provide a theoretical framework for analyzing agency inequalities in WFB: the disjuncture between norms/values and practices and between policies and fathers' capabilities to exercise them. The authors apply the capability framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
0
19

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(179 citation statements)
references
References 31 publications
5
155
0
19
Order By: Relevance
“…Among younger cohorts, more and more fathers seem to embrace the idea of active parenting (Seward et al 2006;Hobson and Fahlén 2009;Smith Koslowski 2011). Their efforts have received increasing policy support at both the national and European levels (Hobson 2002;Moss 2014).…”
Section: Changing Gender Rolesmentioning
confidence: 99%
“…Among younger cohorts, more and more fathers seem to embrace the idea of active parenting (Seward et al 2006;Hobson and Fahlén 2009;Smith Koslowski 2011). Their efforts have received increasing policy support at both the national and European levels (Hobson 2002;Moss 2014).…”
Section: Changing Gender Rolesmentioning
confidence: 99%
“…This definition analytically distinguishes between 'institutional structures' as constraints and 'action' as choice under constraints. In line with this perspective Hobson and Fahlén (2009) have shown that fathers' and mothers' options to enact their specific ideals concerning work and care differ between national gender regimes. Their analysis builds on Sen's (2003) framework of capability and agency.…”
Section: The Interplay Between Institutions and Agency In The Formatimentioning
confidence: 83%
“…We frame the macro-level institutions of interest for our research question in terms of specific features of the welfare state on the one hand and gender culture on the other. Even though actual practices of mothering and fathering may vary, cultural ideas about mothers and fathers often continue to be constructed as distinct and complementary, with motherhood linked to assuming the main responsibility for the child and fatherhood associated with providing the main family income (Hobson and Fahlén 2009). These complementary constructions are closely connected to beliefs in parents' distinct gender dispositions, for instance beliefs in 'maternal love' and a naturally developing 'maternal instinct', signifying the distinctive quality of maternal care due to the existence of a special bond between the mother and the child.…”
Section: Theoretical Mechanisms Investigated In This Bookmentioning
confidence: 99%
“…According to Hobson and Fahlen (2009), CEE countries have the smallest opportunities to achieve a balance between family and work life due to the multiple factors: lower job protection, lack of policies designed to support the father in his family role as well as stronger norms according to which the role of a man is to secure the family's existence. As for mothers in these countries, they have the smallest opportunities to achieve this balance between working and family life.…”
Section: The Model Of Family Policy In the Post-communist Countries Omentioning
confidence: 99%